Mathematical foundations of noise reduction in theatre ballistic missile defence radar systems. (1st January 2014) - Kim, Jaywan; Cho, Byung Rae
In theatre missile defence (TMD), early recognition of an enemy theatre ballistic missile (TBM) firing is one of the most vital factors to ensure a successful missile defence. Satellite sensors usually work as the primary means for early confirmation of the TBM firing in TMD because the sensors would be able to cover the widest possible TBM launch area and they can visually confirm the TBM firing in the early stage of TBM flight. As a result, the sea-based TMD, called the navy theatre missile defence, can offer joint power projections with a vital, flexible, and robust TMD capability. However, the development of decoy tactics associated with TBM's in-flight can cause satellite sensors to go blind and radar is always noise corrupted, thereby generating measurement errors. In this paper, we lay out some mathematical foundations of noise reduction in TBM defence radar systems. The ideas expressed in this paper are those of the authors, and this paper does not represent the views of any agency. Finally, all the references cited in this paper are unclassified documents.